2020
DOI: 10.1371/journal.pone.0235884
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial and spatial-temporal analysis in children’s causal cognition of continuous processes

Abstract: Past research has largely ignored children's ability to conjointly manipulate spatial and temporal information, but there are indications that the capacity to do so may provide important support for reasoning about causal processes. We hypothesised that spatial-temporal thinking is central to children's ability to identify the invisible mechanisms that tie cause and effect together in continuous casual processes, which are focal in primary school science and crucial to understanding of the natural world. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Qualitatively, this explanation differs from the one concluding, for instance, “stone is heavier than the grape.” The former reflects the understanding and coordination of observables with the variants, even in the absence of scientific word knowledge of density. This relaxed scoring system meant that young children were not disqualified due to their developing scientific word knowledge; instead, the focus was on their reasoning and use of variables to think about causal phenomena, as previously used in Dündar-Coecke et al (2019 , 2020) . The inter-judge reliability was further assessed via a colleague peer review, who scored six randomly chosen anonymized and age-blind scoresheets from each year group, resulting in a 100% agreement rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitatively, this explanation differs from the one concluding, for instance, “stone is heavier than the grape.” The former reflects the understanding and coordination of observables with the variants, even in the absence of scientific word knowledge of density. This relaxed scoring system meant that young children were not disqualified due to their developing scientific word knowledge; instead, the focus was on their reasoning and use of variables to think about causal phenomena, as previously used in Dündar-Coecke et al (2019 , 2020) . The inter-judge reliability was further assessed via a colleague peer review, who scored six randomly chosen anonymized and age-blind scoresheets from each year group, resulting in a 100% agreement rate.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that children can acquire causal knowledge from the observation of such natural phenomena typically studied in elementary school science and encountered in everyday life. Such causal tasks require children to engage with mechanism-based thinking, in which underlying causal mechanisms need to be inferred from observable and unobservable structures ( Dündar-Coecke et al, 2019 , 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific method causal tasks were developed by the authors and administered and scored as described for study 2 in Dündar-Coecke et al (2020) . The tasks followed a more realistic scientific procedure, with a sequence of observation, description, prediction, justification, and explanation.…”
Section: Studymentioning
confidence: 99%
“…We have recently begun to study children’s causal thinking in these types of dynamic natural processes, taking an individual difference approach and finding that measures of what we call spatial–temporal analysis were important predictors of children’s thinking about the causal mechanisms involved ( Dündar-Coecke et al, 2019 , 2020 ). Spatial–temporal analysis is the ability to think about how spatial configurations change over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation